Judging and emotion: a socio-legal analysis - Anleu, Sharyn L. Roach (Routledge, Taylor & Francis Group, 2021)
Emotion and everyday judicial work : the context -- Judicial impartiality, emotion, and empathy -- Judicial emotion : experience, display, and management -- Judicial emotion work : others' emotions -- Professional regulation of judicial emotion.